“The houses looked so much alike”: Representations of Contemporary America’s Homogenized, Consumer Society in Ken Kesey’s One Flew Over the Cuckoo’s Nest and Bobbie Ann Mason’s In Country - Parker, Richard Rhett (My University, 2017)
Although Ken Kesey’s One Flew Over the Cuckoo’s Nest (1962) and Bobbie Ann Mason’s In Country (1985) are separated by years and general subject matter, both contain the presence of institutional and cultural forces that seek to persuade individual members of regional American subcultures to accept, whether consciously or unconsciously, the “ideologies” of a larger postmodern American society (which values wealth accumulation, mechanical reproduction, and mass consumption above all). Though some critics, like neo-Marxist Fredric Jameson, use the term “universal standardization” and others, like Rusell Banks, use the term "self-colonization” to describe this process, there seems to be a common thread among these critics that an “American dread” of a patterned life, to borrow the phrasing of Tony Tanner, exists in contemporary American literature. This study, then, seeks to take these concepts, particularly Banks’s notion of “self-colonization,” and expand on the potential metaphorical ties between this “American dread” and the field of postcolonial research and writing. Furthermore, this thesis will chart the similarities and differences that exist within the institutional forces encouraging conformity in the larger American society between the 1960s and the 1980s. It will also attempt to discern the effects that both “colonization” and “self-colonization” had on the subcultures and their members— particularly the mentally ill and Native Americans (for Kesey) and poor, white working- class Southerners (for Mason)—as presented in these novels during their respective time periods.
Chapter I: INTRODUCTION 1 | Chapter II: “THERE WAS THE REBEL AND THERE WAS THE FOLLOWER”: THE AUTOMATION OF THE INDIVIDUAL IN ONE FLEW OVER THE | CUCKOO’S NEST 22 | Chapter III: “THIS TOWN IS DEAD WITHOUT A MALL”: THE “COLONIZATION” OF THE AMERICAN SOUTH IN IN COUNTRY 41 | Chapter IV: CONCLUSION 61 | WORKS CITED AND CONSULTED 71 |
Keywords: Kesey, Ken. One flew over the cuckoo's nest; Capitalism and literature; Mason, Bobbie Ann. In country.; Postcolonialism